Розвиток і становлення організаційного забезпечення діяльності судів в Україні - Коломієць, Н; Пророченко, В; Kolomiets, N; Prorochenko, V (СНУ ім.Лесі Українки, 2019)
У статті висвітлено особливості розвитку і становлення організаційного забезпечення діяльності судів. Розглянуто систему організаційного забезпечення діяльності судів в Україні і теоретичні проблеми організації і правового регулювання забезпечення функціонування судової системи в ході її еволюції. Автори вважають, що історія розвитку національної судової системи знає два основних підходи, що пов’язані із структурною організацією системи судового управління. Перший передбачав наявність відповідних повноважень у Міністерства юстиції та його органів на місцях, а інший - повну концентрацію державно-управлінських повноважень у вищестоящих судових інстанціях. Разом з тим, потреби ефективного здійснення правосуддя за умов побудови правової держави вимагають якісного підняття рівня управління в судовій системі при одночасному реальному дотриманні принципу незалежності суддів. The article is devoted to the research of organizational support of the courts’ work in Ukraine. It highlights the peculiarities of the development and establishment of this organizational support in the context of general issues of the court activity. In the focus of the study is the system of organizational support of the courts in Ukraine and theoretical issues of organization and legal regulation of the judicial system in the context of its evolution. The authors state that the evolution course of the organizational support for the judicial system functioning as a whole and the court activities in particular was extremely complicated and divergent. The development of social relations and the democratization of social processes together with the Declaration of Ukraine's Independence led to the recognition of new democratic values and the adoption of the Constitution of independent Ukraine on June 28, 1996. This normative act as the main law of the state and legal system has become fundamental and significant for the organization and functioning of the entire judicial branch of power in general, as well as organizational support for the activity of courts in particular.
Organizational Support for the Activity of Courts in Ukraine: Establishment and Development
Keywords: суд; судова влада; організаційне забезпечення; організаційне управління; court; judicial power; organizational support; organizational management